Pengaruh Konsentrasi Dosis Injeksi 99TCM–MDP Terhadap Kualitas Citra Kedokteran Nuklir pada Pemeriksaan Bone Scan - Febria Anita; Yadi Isma Nuryadi; Samsun Samsun; Ni Larasati Kartika Sari; Muzilman Muslim (Jurnal Ilmiah Giga, 2023)
Research has been conducted measuring the effect of the dose concentration of syringes on the image of nuclear medicine in order to determine how much influence the dose concentration of syringes has on the image of nuclear medicine. The study was carried out on 35 patients by calculating using the half-life formula and residual dose measurements on syringes that had been used for injection using a dose calibrator. The average residual dose in the syringe was 1.488 mCi, the minimum dose was 0.442 mCi, and the maximum dose of 8.550 mCi. The average activity of the 99Tcm – MDP source injected on a bone scan examination was 11.980 mCi, the average value of postero anterior lumbar vertebrae organ pixels was 37,543, the minimum pixel value was 14,238 and the maximum pixel value was 76,524. The effect of injection dose concentration is seen in the measurement of postero anterior lumbar vertebrae organ with a pixel value of at least 14,238 pixels or 32.23% of the maximum pixel value, influencing the nuclear image, according to the European Association of Nuclear Medicine EANM standard where the vertebral picture is not clear and the visualization of the spinal details in the posterior picture is less clear, the intervertebral disc is less explicit, the appearance of the bone in the sacral region and the iliac sacro joint in the posterior view appears slightly drear. However, the dosage range for patients does not exceed 20 mCi.